2016
DOI: 10.1111/ijpo.12092
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean dietary pattern in pregnant women and offspring risk of overweight and abdominal obesity in early childhood: the INMA birth cohort study

Abstract: Pregnancy adherence to the MD was not associated with childhood overweight risk, but it was associated with lower WC, a marker of abdominal obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(97 citation statements)
references
References 31 publications
(46 reference statements)
3
89
1
Order By: Relevance
“…Few human studies have evaluated the role of maternal diet on childhood obesity risk. A pregnancy cohort study from Spain showed that higher adherence to the Mediterranean diet in pregnancy was associated with lower waist circumference but not with BMI in preschool children , suggesting a specific effect on programming body fat distribution leading to a lower abdominal obesity risk without influencing general obesity. Two other pregnancy cohorts investigated the association between maternal dietary patterns and child body composition and showed no significant associations .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few human studies have evaluated the role of maternal diet on childhood obesity risk. A pregnancy cohort study from Spain showed that higher adherence to the Mediterranean diet in pregnancy was associated with lower waist circumference but not with BMI in preschool children , suggesting a specific effect on programming body fat distribution leading to a lower abdominal obesity risk without influencing general obesity. Two other pregnancy cohorts investigated the association between maternal dietary patterns and child body composition and showed no significant associations .…”
Section: Discussionmentioning
confidence: 99%
“…Several epidemiological studies and clinical trials support the role of the Mediterranean diet in preventing obesity, type 2 diabetes mellitus and metabolic syndrome in adults , while some recent studies suggest a protective role against obesity development in children . In pregnancy, a higher adherence to the Mediterranean diet has been associated with lower risk of preterm birth , higher birth weight and lower offspring waist circumference at preschool age .…”
Section: Introductionmentioning
confidence: 99%
“…[118][119][120][121][122][123][124][125][126][127][128][129][130][131][132][133] Overall, although poor quality diets seem to have detrimental effects in the offspring, they are unlikely to be mediators of changes associated with maternal obesity but probably represent an independent risk factor. Studies have also evaluated the association between type of dietary fat and child health outcomes.…”
Section: Dietary Patterns and Nutrient Changesmentioning
confidence: 99%
“…Six studies assessed dietary patterns during pregnancy and offspring body size (Table ) . Of the six studies, two evaluated adherences to a Mediterranean dietary pattern, three used latent class or principal component analysis to identify dietary patterns, and one assessed a pro‐inflammatory diet score …”
Section: Resultsmentioning
confidence: 99%
“…Adherence to a Mediterranean dietary pattern during the first and second trimesters was inversely associated with offspring body size in early childhood in both studies . Chatzi et al evaluated adherence to the Mediterranean diet in Project Viva (n = 997) and the Rhea Cohort (n = 567) during the first trimester using the Mediterranean diet score, and Fernandez‐Barres et al assessed adherence to the Mediterranean diet in the Infancia y Medio Ambiente Cohort (n = 1827) over the entire pregnancy using the relative Mediterranean diet score. Both studies observed that greater adherence to a Mediterranean dietary pattern was associated with smaller waist circumference among offspring at age 4 years and at ages 6‐10 years .…”
Section: Resultsmentioning
confidence: 99%